Impact of Expanded Insurance Coverage on Racial Disparities in Vascular Disease: Insights From Massachusetts. Issue 4 (April 2016) - Loehrer, Andrew P.; Hawkins, Alexander T.; Auchincloss, Hugh G.; Song, Zirui; Hutter, Matthew M.; Patel, Virendra I.
Abstract : Objective: To evaluate the impact of health insurance expansion on racial disparities in severity of peripheral arterial disease. Background: Lack of insurance and non-white race are associated with increased severity, increased amputation rates, and decreased revascularization rates in patients with peripheral artery disease (PAD). Little is known about how expanded insurance coverage affects disparities in presentation with and management of PAD. The 2006 Massachusetts health reform expanded coverage to 98% of residents and provided the framework for the Affordable Care Act. Methods: We conducted a retrospective cohort study of nonelderly, white and non-white patients admitted with PAD in Massachusetts (MA) and 4 control states. Risk-adjusted difference-in-differences models were used to evaluate changes in probability of presenting with severe disease. Multivariable linear regression models were used to evaluate disparities in disease severity before and after the 2006 health insurance expansion. Results: Before the 2006 MA insurance expansion, non-white patients in both MA and control states had a 12 to 13 percentage-point higher probability of presenting with severe disease ( P < 0.001) than white patients. After the expansion, measured disparities in disease severity by patient race were no longer statistically significant in Massachusetts (+3.0 percentage-point difference, P = 0.385) whereas disparities persisted in control states (+10.0 percentage-point difference, P < 0.001). Overall, non-white patients in MA had an 11.2 percentage-point decreased probability of severe PAD ( P = 0.042) relative to concurrent trends in control states. Conclusions: The 2006 Massachusetts insurance expansion was associated with a decreased probability of patients presenting with severe PAD and resolution of measured racial disparities in severe PAD in MA. Abstract : Supplemental Digital Content is available in the text